What is Context-Sensitive Grammar Sensitive to? - Vanek, Anthony L. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
The goal of linguistics as a science should be a dynamic and cross-culturally sophisticated theory of human communication which reflects what people actually do. The integrating notion of such a theory is that of context — the way in which the particular is made meaningful by interactors. Meaning in context leads the linguist of whatever discipline to a new level of explanation for linguistic form itself — as a means to realize communicative intention.